Proposed productivity increase in sandals production process with Green Productivity approach - Febianti, Evi; S. Mutaqqin, Ade Irman; Amelia, Erien; Muharni, Yusraini (Journal Industrial Servicess, 2023)
Productivity stands as a pivotal determinant of a company's success within the intensifying competition of the industrial world. It signifies the efficiency with which a company utilizes its existing resources. One such company, IKM Permata, generates substantial waste daily while producing hotel sandals. The increasing demand for these sandals corresponds directly to the escalating waste accumulation. Presently, the existing waste remains inadequately managed. In light of these challenges, this study aims to enhance company productivity while concurrently reducing waste. The research seeks to elevate the efficiency of hotel sandal production and address waste generated during the production process. Employing a green productivity approach and a pairwise comparison method, the study yielded results indicating that the optimal alternative could potentially eliminate 1275 kg or 100% of EVA (Ethylene Vinyl Acetate) sponge waste, consequently boosting the GPI (Green Productivity Index) value to 0.0302.